Accuracy Limitations of Interferometric Radar Owing to the Radar Cross Section of Its Antenna - Tegowski, Bartosz; Koelpin, Alexander (IEEE Transactions on Microwave Theory and Techniques, 2024)
This article analyzes the influence of the intrinsic radar cross section (RCS) of interferometric radar systems on their accuracy. The latter is generally considered to be limited by the electrical imperfections and nonlinearities of the radar front-end. However, it will be derived that even if the front-end is ideal and linear, continuous-wave (CW) radars are inherently nonlinear systems. The cause is multiple reflections between the target and the radar antenna, which itself exhibits a nonzero RCS. Although significantly smaller, the secondary reflections superimpose to the primary one, thereby introducing amplitude and phase deviations, which are then erroneously attributed to target displacement. The established model as well as the derived error estimates are verified by measurements with a vector network analyzer and targets with different RCSs.
Created from Fastlane, Scopus look-up
Keywords: Accuracy; antenna radar cross section (RCS); Doppler radar; interferometric radar; radar modeling